The influence of brand association dimensions on consumer loyalty towards health and wellness products in Malaysia - Rafidah Chee Ros (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
The purpose of this study is to examine the influence of brand association dimensions on consumer's loyalty. Specifically, this study examines the relationships between value, perceived quality, trust, endorser associations and consumers' loyalty towards health and wellness products in Malaysia. Based on the associative network theory, four (4) hypotheses have been developed. Target respondents are consumers above 20 years' old who live in the Klang Valley area and have purchased health and wellness products for the last twelve (12) months. Data was collected via a survey instrument, and 197 responses were valid to be analysed. The findings show that all the associations investigated have a significant influence on consumers' loyalty towards health and wellness products in Malaysia. The most significant factor is trust association, followed by perceived quality association, value association and endorser association. The study provides insights to marketing managers for health and supplement products, all the variables are important in developing consumers' loyalty. Hence, for consumers to be loyal in this context, managers need to strategies in a way that the brand is perceived to be trustworthy, delivering good quality and value. A careful selection of endorsers is also critical, as their association with the brand affects consumer loyalty.